A Hydrophobic Small Protein, BpOF4_01690, Is Critical for Alkaliphily of Alkaliphilic Bacillus pseudofirmus OF4 - Takahashi, Tetsuaki; Krulwich, Terry A.; Ito, Masahiro (Frontiers in Microbiology, 2018)
Alkaliphiles grow optimally above pH 9.5 and require Na+ for their growth. Na⁺ cycling across the cytoplasmic membrane is essential for the growth of alkaliphilic Bacillus species at high pH. Proton-motive forces are involved in ATP synthesis by oxidative phosphorylation, but this force is extremely low under highly alkaline conditions. Therefore, unusually efficient ATP synthetic mechanisms have been hypothesized to be employed in these activities. In that context, a monocistronic small protein, BpOF4_01690, was annotated in alkaliphilic Bacillus pseudofirmus OF4. It comprises 59 amino acids and is hydrophobic. Importantly, homologues of this protein were identified only in alkaliphiles. In our study, the mutant with a BpOF4_01690 gene deletion (designated Δ01690) exhibited weaker growth than that of the wild type in both malate-based defined and glucose-based defined media under low-sodium conditions at pH 10.5. Additionally, the enzymatic activity of the respiratory chain of Δ01690 was much lower than that of the wild type. These phenotypes were similar to those of a ctaD deletion mutant and an atpB-F deletion mutant. Therefore, we hypothesize that BpOF4_01690 plays a critical role in oxidative phosphorylation under highly alkaline conditions.